PRAXIOCENTRALISM IN THE PROFESSIONAL STANDARD OF THE TEACHER - L. Y. Monakhova; V. S. Fedotova (Russian State Vocational Pedagogical University, 2017)
Introduction. The main objective of the professional standard, systematizing the work function of a teacher, is to describe not personal qualities of teachers but the process and outcome of their activities. The logic of the development of the professional standard involves the analysis of teaching activities and evaluation of its results, which should possess the properties of measurability and diagnosability.The aim of the present publication is to identify praxiological foundations of the professional standard of the teacher via a comparative analysis of the requirements and fundamental concepts of praxeology - a General theory of successful activities developed by domestic and foreign authors and reflected in monographic and dissertation researches.Methodology and methods of research. Methodological basis of research is the ideas of system, activity and praxiological approaches.Results. The authors prove that pedagogical praxeology as the science and practice of effective organization of pedagogical activity is a new mechanism to describe the characteristics of pedagogical activity and formation of complex of professional portrait of the teacher. Pedagogical praxeology as the mechanism: establishes the framework of competences of the teacher; defines the requirements for structured content, conditions and quality of work of the teacher, their qualifications and competences in the field of professional activity; provides the necessary compliance awareness of teacher's requirements; describes methods of assessing the development of competencies of teachers; promotes the involvement of the teacher in the task of improving the quality of education; serves as the basis for constructing a continuous trajectory of increasing level of professional training of each teacher.Scientific novelty. The content of professional standards from the standpoint of the praxiological approach is investigated; conceptual ideas of praxeology, defining role and position of praxiocentralism in the professional standard are highlighted; criteria and indicators of an estimation of labour activity of the teacher from the point of view of its efficiency and effectiveness are given.Practical significance. This study contributes to the solution of theoretical and practical problems of correlation existing Federal educational state standards (FESS) and professional standards. This is especially important due to the possibility of subsequent approval and implementation into the pedagogical practices of the next generation of FESS developed on the basis of professional standards.